Building the Reputation of Tourism Organizations Based on The Dimensions of Strategic Intelligence - Asst. Prof. Dr. Alaa Abd Al Hussein Radhi, Lect.Mohammed Abd Ali Jasim Al-Shaibani (Scholars Digest Publishing, 2023)
The study aims to demonstrate the impact of strategic intelligence in its dimensions (foresight, future vision, systems thinking, motivation, partnership) on the reputation of tourism organizations. The descriptive analytical approach was adopted mainly in presenting, analyzing and interpreting the study information. The study led to a set of conclusions, the most important of which was It was found that strategic intelligence in all its dimensions and components contributes effectively to achieving all aspects related to the reputation of the tourism organization.
Keywords: Strategic Intelligence, Reputation of Tourism Organizations.